2017
DOI: 10.1055/s-0043-114863
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Minimalist Shod Running Biomechanics and the Acute Response to Running Barefoot

Abstract: The aim of the study was to determine whether habitual minimalist shoe runners present with purported favorable running biomechanithat reduce running injury risk such as initial loading rate. Eighteen minimalist and 16 traditionally cushioned shod runners were assessed when running both in their preferred training shoe and barefoot. Ankle and knee joint kinetics and kinematics, initial rate of loading, and footstrike angle were measured. Sagittal ankle and knee joint stiffness were also calculated. Results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
6
15
0
4
Order By: Relevance
“…Results of this study show that LR on average is significantly increased when switching from shod running to barefoot running which may increase the risk of injury (Zadpoor & Nikooyan, 2011). Our finding coincides with others studies which showed that shod runners on first barefoot attempt may not lower their loading rates (Cheung & Rainbow, 2014;Tam et al, 2017). The observed decrease in stance time also coincides with other studies (De Wit et al, 2000a;Divert et al, 2005;Bonacci et al 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results of this study show that LR on average is significantly increased when switching from shod running to barefoot running which may increase the risk of injury (Zadpoor & Nikooyan, 2011). Our finding coincides with others studies which showed that shod runners on first barefoot attempt may not lower their loading rates (Cheung & Rainbow, 2014;Tam et al, 2017). The observed decrease in stance time also coincides with other studies (De Wit et al, 2000a;Divert et al, 2005;Bonacci et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Some researchers found a reduction in loading rate (LR) in habitual barefoot runners who land on their forefoot (Divert et al, 2005;Lieberman et al, 2010). Other research shows that there is an increase in initial loading rate when switching from shod running to barefoot running (Tam et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Methodological aspects of each study are summarized in Figure 2. In 19 studies, 11,15,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] participants ran on instrumented track; in 18 studies, [12][13][14]17,[34][35][36][37][38][39][40][41][42][43][44][45][46][47] their participants had run on instrumented treadmill; while three [48][49][50] did not inform where participants had run. Regarding running speed, in 21 studies 11,[14][15][16][17][18]24,26,28,…”
Section: Resultsmentioning
confidence: 99%
“…These authors went on to conclude that racing flats are associated with a higher risk of stress fracture of the metatarsal bones compared to training shoes [16]. However, in another study it was reported that whilst shoe construction changes mechanical demands whilst running, runners quickly become habituated to the demands of a given shoe [17].…”
Section: Discussionmentioning
confidence: 99%